Analysis of ‘Investigating an extended multiphase flow model that includes specific interfacial area’, Computer Methods in Applied Mechanics and Engineering, 418:116594, 2024 - Gray, William G.; Miller, Cass T. (Computer methods in applied mechanics and engineering, 2024)
Comments are provided on the recent paper by Ebadi et al. (2024) which demonstrates that the formulated model that was solved contains misconceptions or errors that render the work unsuitable for describing the evolution of interfacial areas in two-fluid porous medium systems. The need for kinematic equations is described and components of a theoretically consistent approach are summarized.